Initial Public Offering Analysis on the Financial Performance of Companies in the Philippine Stock Exchange - Mark Anthony Polinar; John Lemuel Buntigao (Philippine Association of Institutions for Research, Inc., 2021)
The initial public offering (IPO) is one of the money-making moves of a company to raise capital and to have more financial liquidity by selling shares of stocks to the public for the first time. This study concentrated on analyzing the effects of the initial public offering on the financial performance of four companies that went public three years before and three years after 2016 listed in the Philippine Stock Exchange (PSE). The data analysis procedures were accompanied by using the quantitative method that measures the effects of IPO on the financial performance, and t-test statistics are utilized to determine the mean difference between the pre-IPOs and post-IPOs' financial performance. The results indicated that the Return on Sales, Return on the Total Assets, and Return on Equity, Current Ratio, and Debt-to-Equity caused no significant difference in the financial performance of companies before and after the IPO event. In contrast, the Debt Ratio resulted in a significant difference after the IPO event. Thus, by interpreting the results, the study concluded that the debt ratio of the companies improved after IPO listing and signifies that the companies have more assets than liabilities. The implication of the study to various stakeholders such as policymakers, private companies, retail investors, and future researchers was also provided.